2020
DOI: 10.22271/chemi.2020.v8.i5r.10481
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, heritability and character association among yield and yield attributing traits in oats (Avena sativa L)

Abstract: Thirty eight of diverse genotypes oat (Avena sativa L.) were evaluated to examine the genetic variability, heritability, genetic advance, correlation, path coefficient analysis and genetic divergence during rabi 2015-16. Observations were recorded for days to 50% flowering, plant height, number of leaves per plant, flag leaf area, number of tillers per plant, stem girth, number of green pods per spike, length of spike, leaf stem ratio, dry fodder yield and green fodder yield per plant. Analysis of variance rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Through the PCA analysis, among the seven principal factors, PF-1, PF-2 regarded as green fodder yield factors and seed yield factors. Singh et al (2018), Poonia et al (2017), Kumar et al (2006), Yadav et al (2011 and Ahmed et al (2011)also observed similar results of multivariate analysis to the present study. Biplot (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Through the PCA analysis, among the seven principal factors, PF-1, PF-2 regarded as green fodder yield factors and seed yield factors. Singh et al (2018), Poonia et al (2017), Kumar et al (2006), Yadav et al (2011 and Ahmed et al (2011)also observed similar results of multivariate analysis to the present study. Biplot (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies on heritability of oat traits have been published, with heading days, plant height at maturity, and thousand hulled grain weight, being the most commonly traits investigated ( Sürek and Valentine, 1996 ; Yan et al., 2016 ; Kumari et al., 2017 ; Premkumar et al., 2017 ; Chauhan and Singh, 2019 ; Leišová-Svobodová et al., 2019 ; Mazurkievicz et al., 2019 ; Meira et al., 2019 ; Haikka et al., 2020 ; Vanjare et al., 2021 ; Brzozowski et al., 2022 ). However, heritability cannot be generalized to a crop since it is highly specific, and valid only for the material involved in the experiment and the experimental environment ( Majhi, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the genetic diversity of the breeding germplasm, in combination with the phenotypic variation, correlation and heritability of important traits under selection, has facilitated the design of more effective breeding programs ( Nava et al., 2010 ; Krishna et al., 2013 ; Boczkowska et al., 2016 ; Winkler et al., 2016 ; Silveira et al., 2020 ; Cieplak et al., 2021 ). There is published research on this aspect in Sweden, Denmark, Finland, Norway ( Nersting et al., 2006 ), USA ( Winkler et al., 2016 ), India ( Chauhan and Singh, 2019 ), and Brazil ( Mazurkievicz et al., 2019 ; Meira et al., 2019 ; Zimmer et al., 2019 ; Silveira et al., 2020 ), but not under the environmental conditions of southern Chile. Few Chilean oat genotypes have been included in genetic diversity studies ( Achleitner et al., 2008 ), which do not include the newest breeding lines and those most cultivated in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on heritability of oat traits have been published, with heading days, plant height at maturity, and thousand hulled grain weight, being the most commonly traits investigated (Sürek and Valentine, 1996;Yan et al, 2016;Kumari et al, 2017;Premkumar et al, 2017;Chauhan and Singh, 2019;Leisǒva-Svobodováet al, 2019;Mazurkievicz et al, 2019;Meira et al, 2019;Haikka et al, 2020;Vanjare et al, 2021;Brzozowski et al, 2022). However, heritability cannot be generalized to a crop since it is highly specific, and valid only for the material involved in the experiment and the experimental environment (Majhi, 2020).…”
Section: Phenotypic Variation and Heritability Of The Traitsmentioning
confidence: 99%